Green biosynthesis of titanium dioxide nanoparticles incorporated gellan gum hydrogel for biomedical application as wound dressing - Su, Yongtao; Zhu, Xianwei; Xu, Guangqi; Guan, Zhongzheng; Jiao, Wei; Zhang, Zhixin; Sun, Yifei; Wang, Chunlei; Zhang, Rong; Luo, Qianqian; Sui, Ying; Yusoff, Mahani; et al. (Frontiers in Chemistry, 2025)
Titanium dioxide nanoparticles (TiO2NPs) are widely synthesized chemically for industrial applications. However, these methods often have negative environmental impacts, rendering them unsuitable for biomedical applications. Green synthesis approaches offer a promising alternative due to their simplicity, environmental friendliness, and cost-effectiveness. In this study, we report the biosynthesis of TiO2NPs using Morus alba leaf extract and their subsequent incorporation into a gellan gum (GG) biopolymer to create a hydrogel. The physicochemical properties of the biosynthesized TiO2NPs and the TiO2NP@GG hydrogel were characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). Furthermore, the bioactivity of the materials was investigated through antibacterial assays against Staphylococcus aureus and Escherichia coli, as well as in vitro wound healing studies using a 3T3 fibroblast scratch assay. XRD analysis confirmed the successful formation of anatase phase TiO2. SEM images revealed the presence of irregular and rod-shaped TiO2 nanoparticles, with EDS analysis confirming their composition of oxygen and titanium. The particle size was determined to be 80–90 nm, and the nanoparticles exhibited homogeneous distribution throughout the gellan gum biopolymer network. The TiO2NP@GG hydrogel displayed significant antibacterial activity against both S. aureus and E. coli. In vitro wound healing studies using a scratch assay on 3T3 fibroblast cells seeded onto the hydrogel demonstrated a high cell survival rate and enhanced cell migration, suggesting potential for biomedical applications as a wound dressing material.